Role of microglia-mediated neuroinflammation in dysfunction of blood-brain barrier in glioblastoma - Couto, Marina Alexandra Moreira do (2016)
COUTO, Marina Alexandra Moreira do - ROLE OF MICROGLIA-MEDIATED NEUROINFLAMMATION IN DYSFUNCTION OF BLOOD-BRAIN BARRIER IN GLIOBLASTOMA. Coimbra : [s.n.], 2016. Dissertação de Mestrado.